The American - Russian competition in the Middle East (natural gas as a model) - Rami .Q. Abboud (Journal of Madenat Alelem University College, 2022)
The issue of energy is an important axis at the global level because of its vital role in economic development in all areas of life, especially in light of the increasing global demand for energy resources The Middle East region has gained great importance in the field of natural gas, given the huge reserves in the region, the strategic and geopolitical importance of the Middle East made it an international competition for energy resources in the region, especially natural gas, among the countries of the region. Natural gas lines and networks, in addition to the huge gas reserves in the region, and what distinguishes the Middle East is: It is a complete transit area, and for this reason and others it is a hot area and an arena of competition and conflict in it. Various parties, especially the Russian-American competition.